1999
DOI: 10.1292/jvms.61.227
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological Distributions of Fibronectin, Tenascin, Type I, III and IV Collagens, and Laminin during Tooth Development and Degeneration in Fetuses of Minke Whale, Balaenoptera acutorostrata.

Abstract: ABSTRACT. The immunohistological distributions of fibronectin, tenascin, type I, III and IV collagens, and laminin were observed in the tooth buds of fetuses of minke whale, Balaenoptera acutorostrata. Distributions of extracellular matrices (ECMs) examined in this study except for tenascin were generally similar to those of terrestrial mammalian species during development of the tooth bud. Tenascin in the fetuses of minke whale showed characteristic distributions in the dental lamina and the enamel organ in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…We found that one baleen whale (bowhead) had an intact DPP domain that looks very much like other mammals including the relatively closely related dolphins (Figure 3). It turns out, however, that fetuses of at least some baleen whale species develop and then resorb before birth, a dentin-like tooth structure that lacks an enamel covering [39,41]. It is not known if the retention of the DPP domain in these animals is due to selective pressures associated with: 1) the direct production of dentin in their embryonic tooth structures; 2) DPP released during the biosynthesis of these temporary teeth modulating the responses of other nearby tissues (e.g., baleen); or 3) critical expression of DPP in the kidney or some other non-dental tissue.…”
Section: Resultsmentioning
confidence: 99%
“…We found that one baleen whale (bowhead) had an intact DPP domain that looks very much like other mammals including the relatively closely related dolphins (Figure 3). It turns out, however, that fetuses of at least some baleen whale species develop and then resorb before birth, a dentin-like tooth structure that lacks an enamel covering [39,41]. It is not known if the retention of the DPP domain in these animals is due to selective pressures associated with: 1) the direct production of dentin in their embryonic tooth structures; 2) DPP released during the biosynthesis of these temporary teeth modulating the responses of other nearby tissues (e.g., baleen); or 3) critical expression of DPP in the kidney or some other non-dental tissue.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was described in detail already in earlier times (Kükenthal, ) as well as in recent publications (Deméré et al, ). Like in all therians, the tooth germs pass during their development through bud, cap, and bell stages but do not reach the crown stage before degradation by odontoclasts, macrophages, and a number of enzymes (Ishikawa and Amasaki, ; Ishikawa et al, ). Ishikawa and Amasaki () show for the minke whale that this species does not develop ameloblasts and in consequence no enamel is formed.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, histological studies have attempted to understand the developmental patterns for tooth buds and baleen origin in the context of growth factors and molecular signaling (Ishikawa et al, 1999). While these authors commented neither on homodonty nor double teeth, they argued that resorption mirrors the mechanism of tooth shedding in diphyodont mammals.…”
Section: Double Teethmentioning
confidence: 99%
“…While these authors commented neither on homodonty nor double teeth, they argued that resorption mirrors the mechanism of tooth shedding in diphyodont mammals. However, they noted that, in diphyodont mammals, only the root of the deciduous tooth undergoes resorption, whereas in mysticete embryos the entire tooth is resorbed (Ishikawa et al, 1999). Clearly, further investigations should focus on more in-depth histological work about the homology of the tooth buds, their morphology, and the differences in these traits across a wider ontogenetic series, along with interspecific comparisons across mysticete species.…”
Section: Double Teethmentioning
confidence: 99%